Bridging the Gap: Link-and-Match Strategy for Sharia Economics Graduates in Islamic Non-Bank Financial Institutions - Rahmawati, Naili; Bonang, Dahlia; Ismail, Shafinar (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2025)
Purpose:This study examines the link and match strategy in higher education to bridge the gap between graduates' skills and industry demands, particularly in the Islamic Non-Bank Financial Industry (IKNB Syariah). By adopting Human Capital Theory, this research highlights the importance of aligning university curricula with labor market needs to enhance graduates' employability.Design/Methodology:A qualitative research approach with an inductive methodology was used to explore the effectiveness of link and match policies. Data were collected through semi-structured interviews and focus group discussions (FGD) with 40 respondents, including students, government officials, education experts, and industry practitionersFindings:The study identifies curriculum misalignment, limited industry engagement, inadequate internship programs, and a lack of technology integration as key barriers to the effectiveness of link and match. However, competency-based curricula, industry partnerships, graduate involvement, and digital learning adoption significantly support graduate readiness for the workforcePractical Implications:Strengthening university-industry collaboration, implementing professional certification programs, and integrating technology into learning are crucial strategies to enhance the effectiveness of link-and-match policiesOriginality/Value:This research provides a comprehensive analysis of the link and match strategy in Sharia economics education, emphasizing the role of Islamic finance industry collaboration in improving graduate employability